Analisis Manajemen Keuangan Sekolah Pada Sekolah Menengah Kejuruan (SMK) - Indriawati, Prita; Suyanti, Ririn (Rifa'Institute, 2022)
Education management itself is seen as a process needed in the world of education to achieve the goals of education itself. The purpose of this paper is to explore school financial management in Vocational High Schools (SMK), as well as to find out the effectiveness of existing financial management in schools. The school used as the object was SMK N 2 Balikpapan with research informants namely the school principal, vice principal for finance, school treasurer, and committee. Based on the research, it was found that the main source of school finance came from BOS funds. The management process begins with deliberations and holding meetings of all teachers and employees with the process of preparing the RKAS and preparing the RAB, based on the plans needed by the school which will first be considered by the School Committee. Realization of school financial management sourced from BOS funds and school committee funds in Vocational High Schools for the 2021/2022 academic year has been carried out efficiently financial While the inhibiting factor is still a lack of BOS funds and school committee funds provided to support the process of school facilities and infrastructure or in other words not in accordance with the previous plan for its realization.